An Interface Circuit For Agriculture Sensor - Soh, Yan Ying (Universiti Sains Malaysia, 2017)
Agriculture sensors play an important role in modern agriculture. The use of sensors in various agriculture sectors minimises the environmental impact on crops, helps in increasing yield and saving cost of operation. Among all agriculture industries in Malaysia, the mushroom industry is a comparatively new and small industry. The production of mushrooms in Malaysia is unable to meet the demand in local markets. Import of mushrooms has been increasing every year and the amount has reached 10 million tons of mushrooms in 2012. As most of the mushroom farms in Malaysia are small-scaled, their production capability is limited by inadequate environmental control system and the lack of financial resources to upgrade the systems. This project presents an agriculture sensor interface circuit to monitor and control the environmental conditions in a mushroom farm. It utilizes a temperature and humidity sensor, a carbon dioxide sensor and a light dependent resistor, the Arduino Uno microcontroller board, a Wi-Fi module. The system is able to acquire data from the sensors that are placed in the mushroom farm and send the data to ThingSpeak cloud for storage. The data can be accessed via ThingSpeak and an Android app designed alongside the project. Arduino Uno is used to process data acquired from the sensors and control the appliances such as humidifier, fan and light in the mushroom farm to regulate the environmental condition. The temperature, humidity, carbon dioxide and the light measured using the circuit developed have percentage error as low as 0.4%, 1.5%, 2.2% and 1.34% respectively.